Homocystinuria: Literature Review and Clinical Case Description - Natalia V. Buchinskaya; Eugenia A. Isupova; Mikhail M. Kostik ("Paediatrician" Publishers LLC, 2019)
Homocystinuria is rare autosomal-recessive monogenic disorder associated with disturbance of methionine metabolism due to liver enzyme cystathionine--synthetase (CBS) deficit. That in turn causes elevated concentration of homocystein and its metabolites in blood and urine. The main clinical manifestations of homocystinuria are: myopia, ectopia lentis, psychomotor retardation, learning difficulties, mental retardation, mental illnesses, behaviour problems, paroxysms, extrapyramidal symptoms, skeletal anomalies (body height), long limbs - dolichostenomelia and arachnodactylia (Marfan Phenotype), pectus carinatum, valgus lower limbs, scoliosis, osteoporosis, thromboembolic disorders. Diagnostics of homocystinuria is based on clinical findings and laboratory changes (increase of methionine and homocysteine levels in serum). There is prenatal and DNA-diagnostics (genetic variants in CBS gene). Revealing of homocystinuria demands examination of first-degree relatives. Therapy of patients with homocystinuria includes not only diet therapy but also pyridoxine, folic acid, betaine administration. Syndromic concomitant therapy is also used. The description of the patient with severe B6-resistant form of homocystinuria is given in this article.